Techno-economic evaluation of a frost-free air source heat pump water heater. (June 2020) - Wang, Zhihua; Li, Guichen; Wang, Fenghao; Li, Kehua; Lou, Yechun
Highlights: A techno-economic analysis on the frost-free ASHP system was analyzed and compared. The running cost reduced 23.2, 23.6 and 29.0 % compared with the reference system. The payback period of the initial cost is about 3.3–4.2 years. The studied system was a promising economical way for space heating. Abstract: In order to improve the performance of air source heat pumps (AHSPs) when it is operated in winter, a novel frost-free ASHP system has been developed and the thermodynamic characteristics was performed in the previous work. Before it is large-scale promoted and applied, an economic analysis should be conducted. However, there is little research on the economic analysis of the system, which limits the development and application of innovation technologies. Therefore, a techno-economic analysis of the system was evaluated in typical climate zones in China and compared with a conventional ASHP unit in this paper. The results showed that the running cost of the frost-free ASHP system reduced 23.2, 23.6 and 29.0 % in comparison with the conversional ASHP system in Xi'an, Shenyang and Hefei cities respectively, also, corresponding to the payback period of the initial cost were 4.2 years, 3.3 years and 4.03 years respectively. It shows that the frost-free ASHP system is a promising economical way for space heating. Conclusion from this work will provide key information for the user in decision making and determining the economic viability of the frost-free ASHP system has been evaluated before it is large-scale promoted and applied.